2023
DOI: 10.1186/s12888-023-05137-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the neglected anxiety disorder: validation of the social anxiety spectrum-short version (SHY-SV) questionnaire

Liliana Dell’Osso,
Ivan Mirko Cremone,
Benedetta Nardi
et al.

Abstract: Background In the recent years, a growing body of literature stressed the importance of a dimensional perspective on mental disorders. In particular, since its conceptualization, one of the main concerns in the field of Social Anxiety Disorder (SAD) has been the definition of a diagnostic threshold, leading to the suggestion that SAD may be more properly classified as a spectrum of severity rather than a discrete disorder based on subjectively determined threshold. The purpose of the current re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Both the total and domain scores had great test-retest reliability with all ICCs above the value of 0.90. The Pearson's coefficients for the SHY-SV domain scores ranged from 0.391 to 0.933, and they were positively and significantly correlated with one another (p 0.001) [50]. The questionnaire was developed as a shortened and updated version of the SHY-SR, the first questionnaire specifically designed as a dimensional approach to the social anxiety spectrum, which was proven useful in previous research [51].…”
Section: The Shy-sv Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Both the total and domain scores had great test-retest reliability with all ICCs above the value of 0.90. The Pearson's coefficients for the SHY-SV domain scores ranged from 0.391 to 0.933, and they were positively and significantly correlated with one another (p 0.001) [50]. The questionnaire was developed as a shortened and updated version of the SHY-SR, the first questionnaire specifically designed as a dimensional approach to the social anxiety spectrum, which was proven useful in previous research [51].…”
Section: The Shy-sv Questionnairementioning
confidence: 99%
“…The SHY-SV is a questionnaire designed by Dell'Osso et al [50] for the evaluation of the whole spectrum of social anxiety, including common manifestations, atypical symptoms, and personality traits, comprising 139 items organized in 5 domains (Interpersonal sensitivity, Behavioral inhibition, Performance, Social situations, and Substance Abuse) and one appendix (Childhood and adolescence). Each item's answers are coded in a dichotomous way (yes/no) and the scores relating to the individual domains and appendix are calculated by counting the number of positive answers.…”
Section: The Shy-sv Questionnairementioning
confidence: 99%
“…The answers to the various items are coded in a dichotomous way (yes/no) and the scores relating to the single domains and appendices are obtained by counting the number of positive answers. The SHY-SV was developed by Dell'Osso et al (37); the validation study reported strong internal consistency, great testretest reliability and convergent validity with other dimensional measures of SAD.…”
Section: Social Anxiety Spectrum -Short Version Questionnairementioning
confidence: 99%
“…The questionnaire had a high internal consistency, strong inter-rater reliability, and discriminant validity and throughout the years it has been employed in a variety of clinical contexts throughout the last few decades (7,33,35,36). However, due to the excessively long time for its compilation and some outmoded and superfluous items, recently its application in routine clinical practice has been difficult; for this reason, the same authors recently proposed a shortened and renewed version, the Social Anxiety Spectrum -Short Version (SHY-SV) (37).…”
Section: Introductionmentioning
confidence: 99%